Does platform type matter? A semantic analysis of user attitude formation on online platforms - Zhang, Liangbo; Zhan, Ge; Li, Qijing; Ren, Jifan (Frontiers in Psychology, 2022)
Online platform is a setting where consumers may express their attitude in text or visual content, but the semantic meanings of user-generated content (UGC) have not been extensively studied in psychology literature. We gathered 7,264 lines of unstructured online reviews about two famous brands on two types of social media platforms: online text-based forums and live-streaming platforms. The data were collected through a web crawler, and semantic analysis was employed to process the data before hypothesis testing. The findings of this study indicate that online product and brand perception in terms of information richness, perceived price and culture distance, significantly influence user attitude. Compared with traditional text-based platforms, contents in live-streaming platforms with less product features, wider culture distance and lower perceived price are favored among users. This study contributes to interactive marketing literature by investigating different types of digital platforms with a semantic analysis approach.